2000
DOI: 10.1051/aas:2000222
|View full text |Cite
|
Sign up to set email alerts
|

Optical observations of five X-ray selected BL Lacertae objects

Abstract: Abstract. We present optical data obtained with the 1.05 m telescope of the Torino Astronomical Observatory for five X-ray selected BL Lacertae objects. The data are in the Johnson's B, V , and Cousins' R bands. As the observing periods include the pointings of the Satellite per Astronomia X "Beppo" (BeppoSAX), our optical information will be comparable with the X-ray observations for a better understanding of the properties of these objects. The present data also provide optical information on sources that ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 13 publications
1
42
1
1
Order By: Relevance
“…It exhibits significant optical polarization (Feigelson et al 1986) and variability (Villata et al 2000). The host galaxy was resolved in ground-based images by Feigelson et al (1986), Falomo (1996, and Nilsson et al (2003).…”
Section: Results For Individual Objectsmentioning
confidence: 99%
“…It exhibits significant optical polarization (Feigelson et al 1986) and variability (Villata et al 2000). The host galaxy was resolved in ground-based images by Feigelson et al (1986), Falomo (1996, and Nilsson et al (2003).…”
Section: Results For Individual Objectsmentioning
confidence: 99%
“…Optical data were taken from the literature and for some objects determined using the Calar Alto 1.23 m telescope (Beckmann 2000a). A campaign for simultaneous optical data has also been performed for a few objects (Villata et al 2000). Variability in the optical band is not expected to be large: all objects presented here are X-ray dominated objects (i.e.…”
Section: Spectral Energy Distributionmentioning
confidence: 99%
“…Multiple photometric optical values were found in the literature, showing a great variation of the source brightness in the optical band from V ¼ 16 to V ¼ 12:8. A complete study of the optical band can be found in Villata et al (2000), where variability on short timescales (a few days) was reported.…”
Section: Introductionmentioning
confidence: 99%